The Role Of The Religious Youth Harmoniy Forum (FKPUB) In Improving Local Wisdom-Based Religious Moderation In Pamekasan City - Andri Sutrisno; Fitrah Sugiarto (Khatulistiwa, 2022)
Religious harmony and local wisdom are an inseparable part of improving religious moderation in the city of Pamekasan. FKPUB's role in the very good where they apply local wisdom solely to make Pamekasan as a city that attaches importance to the value of religious moderation rather than differences in religion. The birth of FKPUB and the application of local wisdom brought people to have a tolerant attitude and harmony between religious diversity in the city of Pamekasan. The purpose of this study is to be able to understand about the social setting of FKPUB and the social construction of the pamekasan community, understand the social interaction of multi-religious communities in the city of Pamekasan and know about the FKPUB war in applying local culture in the city of Pamekasan. As for this research method, using a descriptive qualitative approach to the paradigm of social construction and social interaction with this type of field research. While the data collection techniques researchers use in observation, interview and documentation techniques. Thus generating three data analyses, namely data reduction, data presentation and conclusions. The results of this study can be described in the form of three results, namely 1. Social construction built by FKPUB through three very important roles, namely extensization; where there is a law legalized by the ministry of religion so that the community lives in the framework of harmony between others and the inauguration of the regent pamekasana, objectivation; that FKPUB was born because there is a desire from young people to live in harmony between religions and internalization; There is a practical movement carried out by FKPUB in the form of social services, gotong royong and orphan compensation. 2. Inter-community social interaction conducted by FKPUB by conducting Talk show Seminars and studies every month in improving religious moderation. 3. Local wisdom applied by FKPUB in pamekasan city is rembhek (discussion) and rampa' naong baringin korong (lush shaded shade of cage).